PENGHALANG KEWARISAN DALAM PASAL 173 HURUF (a) KOMPILASI HUKUM ISLAM - Ahda Fithriani (Syariah: Jurnal Hukum dan Pemikiran, 2015)
The presence of Article 173 (a) Compilation of Islamic Law brought changes in Indonesia because Islamic inheritance particularly attempted murder and persecution to enter weight as a barrier inheritance. Previously, jurists agreed only three things that make an unobstructed heir to inherit that slavery, religious differences, and murder. Through the viewpoint of Islamic law, attempted murder and persecution weight of a renewal in Islamic law which is supported by one of the methods of ijtihad is sadd al-zari'at. Methods sadd al-zari'at closed the road for someone to expedite the distribution of the estate with attempted murder and severe persecution against muwarris. Through this method, the inheritance rights of the offender will be hindered because of his actions.